1992
DOI: 10.1083/jcb.119.3.583
|View full text |Cite
|
Sign up to set email alerts
|

Role of astral microtubules and actin in spindle orientation and migration in the budding yeast, Saccharomyces cerevisiae.

Abstract: Abstract. In the yeast Saccharomyces cerevisiae, before the onset of anaphase, the spindle apparatus is always positioned with one spindle pole at, or through, the neck between the mother cell and the growing bud. This spindle orientation enables proper chromosome segregation to occur during anaphase, allowing one replicated genome to be segregated into the bud and the other to remain in the mother cell. In this study, we synchronized a population of cells before the onset of anaphase such that >90% of the cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
249
2
2

Year Published

1996
1996
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 297 publications
(262 citation statements)
references
References 37 publications
7
249
2
2
Order By: Relevance
“…Thus, the fluorescence measurement is an indirect indication of the relative amount of F-actin in the cell at the time of fixation. Using this method, Lillie and Brown [17] have shown that a shift to high temperature causes a rapid but transient depolymerization of actin, which is accompanied by a transient redistribution of actin-containing structures [17,19,20]. Similar effects on actin organization have been noted upon increasing the osmotic strength of the medium [211.…”
Section: Resultsmentioning
confidence: 72%
“…Thus, the fluorescence measurement is an indirect indication of the relative amount of F-actin in the cell at the time of fixation. Using this method, Lillie and Brown [17] have shown that a shift to high temperature causes a rapid but transient depolymerization of actin, which is accompanied by a transient redistribution of actin-containing structures [17,19,20]. Similar effects on actin organization have been noted upon increasing the osmotic strength of the medium [211.…”
Section: Resultsmentioning
confidence: 72%
“…Many but not all MT-related events are affected, including the formation of a normal mitotic spindle and thus normal chromosome segregation (Hartwell et al, 1973;Byers and Goetsch 1974;Sethi et al, 1991) and karyogamy (Sethi et al, 1991). Movement of the nucleus to the bud neck, which depends on the presence of astral MTs (Palmer et al, 1992), is not affected in cdc2O cells, but this role of MTs may not rely on dynamic MT behavior. Although it is unlikely that the Cdc2Op is associated directly with MTs, its role may be to promote MT disassembly through a mechanism that also affects the proteolysis of proteins in other pathways.…”
Section: Discussionmentioning
confidence: 99%
“…The yeast actin cytoskeleton has been shown to be involved, not only in late mitotic events such as septum formation and cytokinesis, but also in directing cell wall deposition at the growing region of the cell [5,6]. In the budding yeast Schizosaccharomyces cerevisiae, actin function is also required to maintain proper spindle orientation prior to the onset of anaphase [7]. All these events are, thus, essential for proper chromosome distribution, by which daughter cells inherit a complete set of genetic information required for the next cell cycle.…”
Section: Introductionmentioning
confidence: 99%